RAINFALL RUNOFF PERFORMANCE OF SMALL SCALE GREEN ROOFS SYSTEM (Malaysian Journal of Civil Engineering, 2018)
As green roof technology is still emerging, there is limited rainfall runoff data available at present under Malaysian climate. Located at equatorial region, Malaysia will sometimes experience high humidity and high temperatures throughout the year. Hence this study will present the initial outcomes of the joint initiative between Malaysia Agricultural Research and Development (MARDI) and Universiti Tun Hussein Onn Malaysia (UTHM) in promoting this green roof technology in Malaysia. The study aims to provide initial observation on rainfall runoff performance using the green roofs set up by MARDI. Initially this green roofs system were set up for the agriculture study of three different vegetation and two treatment systems which known as conventional and self-watering system, under two different substrate depths which are 50 mm and 100 mm. Six rainfall events were manually observed consists of one extreme rainfall and five moderate rainfall type. It is found that the highest retention from the event with total rainfall of 94.7 mm was 49.8% for 5SWLC (50 mm substrate depth + self-watering system + Lantana camara) but the retention varied between 38.1% and 47.0% for moderate rainfall range between 30.3 mm and 35.4 mm for the same roof treatment. At the same time, the other treatment systems with other type of vegetation and depths show lesser retention than the 5SWLC. It can be concluded that with the additional storage system, may increase the typical total retention for green roofs.